Pakistan-India Equation: Determinants, Dynamics and the Outlook. (1st January 2017) - ,
Abstract : Though it has been a longtime since 1947, both Pakistan and India couldn't steer the trajectory of their relations in the right direction. Even in the twenty first Century, this relationship is, by and large, determined through the prism of history. The nuclearization of South Asia, triggered by India and the strategic arms race alongside perpetual state of conflict, have aggravated the threat of war that may no more remain limited or restricted to convectional arsenal; but has strong indicators of escalation of any future conflict to nuclear plane, leading to Mutual Assured Destruction (MAD.) The assumption that economic interdependence can lead to normalization of relations, has failed in this particular case. The determinants and dynamics of bilateral relations, holdout that normalization of relations is a complex phenomenon intricately embedded in the resolution of the core disputes. Be it the domain of military and strategic relationship, or either political or economic dimension, there has been no substantial improvement. The resolution of the core disputes including Kashmir is the key to the betterment of relations, which remains as an unfulfilled agenda in the United Nations. Bilateralism has failed so far, and there is a dire need for a sustainable conflict resolution mechanism assisted by third party mediation in order to restraint the region from arm race and the threat of nuclear war, and to ensure a prosperous and peaceful future for South Asia.